Drug utilisation evaluation study on patients with diabetes mellitus among Rohingya refugees in IMARET mobile clinic - Mohamed Tahir, Ahmad Rashidi; Agussaiful, Nurasmaa; Ahmad Hisham, Shairyzah; Abdul Rashid, Aneesa; Yahaya, Ahmad Yusuf; Devaraj, Navin Kumar (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: Since 1978, Rohingya refugees have fled from their native nation, Myanmar to escape ethnic prosecution. They comprise of the Muslim minority ethnic group originating from the Rakhine state in Myanmar. In many host countries, they may have difficulty to access health care services. The Islamic Association of Malaysia (IMAM) Response and Relief Team (IMARET) have taken many initiatives to provide healthcare services to the refugees through their volunteer-led mobile clinics. Therefore, this study aims to evaluate the utilisation of drugs among type 2 diabetes mellitus (T2DM) patients visiting this clinic. Methods: This was a cross-sectional study among Rohingya refugees with T2DM that visited the IMARET mobile clinics from August until November 2017. Convenient sampling method was used. Data were collected through patient’s interview, review of the patient’s prescriptions and their HbA1c readings. Results: A total of 29 T2DM patients were included in this study. The majority were female (75.9%) and aged below 65 years old (75.9%). The most commonly prescribed anti-diabetic agent was metformin (72.2%), followed by glibenclamide (22.2%) and gliclazide (5.6%). Metformin as a monotherapy (31%) was the most frequent treatment prescribed. More patients had controlled T2DM (62.1%) compared to those with uncontrolled DM. We found 90.9% of patients who were treated according to the recommended DM guidelines achieved a good blood glucose control (p=0.02). Conclusion: In Rohingya refugees having T2DM who were treated in the IMARET mobile clinic, the percentage having good control DM status is higher in those whose treatment regimen adheres to the clinical practice guidelines.